Regulation of Multiple Core Spliceosomal Proteins by Alternative Splicing-Coupled Nonsense-Mediated mRNA Decay - Saltzman, Arneet L. (American Society for Microbiology (ASM), 2008)
Alternative splicing (AS) can regulate gene expression by introducing premature termination codons (PTCs) into spliced mRNA that subsequently elicit transcript degradation by the nonsense-mediated mRNA decay (NMD) pathway. However, the range of cellular functions controlled by this process and the factors required are poorly understood. By quantitative AS microarray profiling, we find that there are significant overlaps among the sets of PTC-introducing AS events affected by individual knockdown of the three core human NMD factors, Up-Frameshift 1 (UPF1), UPF2, and UPF3X/B. However, the levels of some PTC-containing splice variants are less or not detectably affected by the knockdown of UPF2 and/or UPF3X, compared with the knockdown of UPF1. The intron sequences flanking the affected alternative exons are often highly conserved, suggesting important regulatory roles for these AS events. The corresponding genes represent diverse cellular functions, and surprisingly, many encode core spliceosomal proteins and assembly factors. We further show that conserved, PTC-introducing AS events are enriched in genes that encode core spliceosomal proteins. Where tested, altering the expression levels of these core spliceosomal components affects the regulation of PTC-containing splice variants from the corresponding genes. Together, our results show that AS-coupled NMD can have different UPF factor requirements and is likely to regulate many general components of the spliceosome. The results further implicate general spliceosomal components in AS regulation.